Readings in microeconomics - Breit, William; Hochman, Harold M. (New York : Holt, Rinehart and Winston, 1971)
The papers reprinted in this volume, as in the first edition, focus on the logic, methodology, and applications of microeconomics. Most of the selected articles emphasize conceptual rather than empirical material and articles that can be readily understood without significant formal training in any mathematics more advanced than geometry and, in a few cases, elementary calculus. In revising the book, ten selections have been added and six of the original articles have been omitted.
Includes bibliographical references and index.
rpm 12/09/2017
Loans
Keywords: Microeconomics